STUDENTS’ PROBLEMS IN WRITING COMPOUND SENTENCES - Silviana Fadhilah (Universitas Bung Hatta, 2022)
The purpose of this research was to describe the third year students’ problems in writing compound sentences expressing contrast, reason, and additional idea at English Department of Bung Hatta University. Descriptive method was used as the design of this research. The number of population members was 53 students. The writer used total sampling technique to select the sample. Writing test was the instrument to get the data. The students were asked to write 21 compound sentences : 7 sentences expressing contrast, 7 sentences expressing reason, and 7 sentences expressing additional idea. The test was reliable because the reliability of the test was high (0.98).The result of this research showed that generally the third year students at English Department of Bung Hatta University had problem in writing compound sentences. They had problems in writing compound sentences expressing contrast, reason, and additional idea. Among those problems, the most problem the students face was writing compound sentences expressing reason (39.49%). In writing compound sentences expressing reason, the most problem the students face was in mechanics (41.06%), especially in punctuation (25.13%).Dealing with the conclusion, the writer suggested to the lecturers to use matching picture as the media to teach compound sentence to the students. The students are suggested to do more exercises in writing compound sentences expressing reason by using matching pictures. The next writers are expected to find out students’ problems in writing compound sentences in other conjunction such as compound sentences with semicolon, correlative conjunction, and conjunctive adverbs. REFERENCES Brandon, Lee & Kelly Brandon. (2011). Paragraph and Essays with Integrated Readings (11thed). Boston : Wadsworth Cengange Learning. Cahyo, Fuad Nur. (2013). Using The Mind Mapping Technique To Improve The English Writing Skill of The Tenth Grade at MAN Yogyakarta III in The Academic Year 2012/2013. (S1 Degree). Online Publish Thesis. Universitas Negeri Yogyakarta. Gay, L.R, Geoffrey E. Mills, & Peter Airasian. (2009). Educational Research : Competencies for Analysis and Application. Upper Saddle River, New Jersey : Pearson Education, Inc. Lauder, Allan. (2008). The Status and Function of English in Indonesia : A Review of Key Factors. Makara, Sosial Humaniora.,12(1),1-12. McMillan, James. H. (1996). Educational Researh : Fundamentals for the Consumer. (2nded). New York: HarperCollins Publishers, Inc. Sudijono, Anas. (2015). Pengantar Statistik Pendidikan. Jakarta: Rajawali Pers. Usman, Husaini & Purnomo Setiady Akbar. (2011). Pengantar Statistika. Jakarta : Bumi Aksara.